Assessing Vulnerability of Agriculture to Drought in East Java, Indonesia: Application of GIS and AHP - Mulyanti, Heri; Istadi, Istadi; Gernowo, Rahmat (Department of Urban and Regional Planning, Diponegoro University, 2023)
Drought known as ‘silent killer’—unpredictable slow-moving hazard which cause severe damage to people and environment. Since agriculture is the first and foremost sector affected by drought, the risk of crop failure can be minimized by reducing vulnerability. Climate patterns can be considered as systematic conditions which are capable of assigning sensitivity regions to drought. Here, the study employs Oldeman’s Agro Climatic data as physical vulnerability indicator to assess and monitor the vulnerability of agriculture system to drought in East Java. The study used long-term monthly rainfall observation data to generate climatic map accompanied with socio-economic indicators to assess vulnerability of region to drought. Spatial distribution of vulnerability was mapped using Geographic Information Systems (GIS) combined with Analytic Hierarchy Process (AHP). The results show there are five categories of vulnerability to drought: very high, high, moderate, low, and very low based on standardized index. Madura Island, particularly Bangkalan, Sampang, and Sumenep considered as most vulnerable region to drought. In addition, most regions in the north plain of East Java, including Tuban, Lamongan, and Gresik categorized as highly vulnerable to drought. Factors affecting vulnerability are mostly related to drier climate which affect acreage and availability of irrigation. The socio-economic factors likewise smallholder farmers and poverty contribute to rising vulnerability level. South part of East Java, particularly Tulungagung and Blitar Regency was least vulnerable because of appropriate climate which induced to acreage of irrigated land. The study emphasizes the utilizing of Oldeman climate pattern as primary indicator in determining vulnerable regions. Smallholder farmers and poverty causing vulnerability in agriculture emerged as priority for further study. The results can provide new insights into drought management for most vulnerable regions by considering local climatic characteristics.